Delimitation of Channel Migration Zones in the Rapti River Basin, Middle Ganga Plains - Rana, Narendra Kumar (National Geographical Journal of India, 2022)
Channel migration is an important geomorphological process in the floodplain area. The rapid shifting of rivers has not only complicated the flood problems but also undermined engineering structures and pose constant threat to public infrastructure. In these areas risk minimization through channel migration zoning forms the core of river management programme. The present study on river Rapti analysed historical information and field data to interpret past and present channel conditions in order to predict future channel behaviour and areas at risk of channel movements. River Rapti is a foothill-fed river originating from the Siwalik hill areas of Nepal and draining the interfan areas between the Gandak and the Ghaghra. The river is known for its frequent channel movement. Several studies based on conventional and historical data confirmed its unpredictable channel behavior. This study delineated boundary of the channel migration zone (CMZ) with the help of geospatial data ranging a period of over 70 years and limited field survey. The CMZ is the cumulating product of the Historical Migration Zone, the Avulsion Hazard Zone, the Erosion Hazard Area and the Disconnected Migration Area. The river Rapti being a foothill-fed river exhibit spatial variations in channel migration throughout its course. Several broad patches of CMZ are observed along its lower course where there is concentration of human settlements, economic activities and infrastructure. The study found that constant channel migration is undermining various engineering structures, eroding valuable and productive agricultural land and enhancing vulnerability of the floodplain dwellers. The study further recommended that site suitability analysis should be undertaken prior to construction of any engineering structures including public infrastructure